Trends in the management of policy volatility: managing internal policy risk in three OECD countries. (24th November 2022) - Howlett, Michael; Leong, Ching; Sahu, Sonam
Most studies of risk management examine only exogenous risks - that is, those external to the policy-making process such as the impact of climate change, extreme weather events, natural disasters or financial calamities. But there is also a large second area of concern - 'internal risks' or those linked to adverse or malicious behaviour on the part of policymakers. This behaviour to deceive or 'game' the intentions and expectations of government is a part of the policy world which also requires risk management. The paper reviews three archetypal cases of efforts to manage this side of policy risk in the UK, the USA and Australia and draws lessons from them about how this 'dark side' of policy-making can be managed.